"It's not the end of the story:" Understanding the continued recovery from homelessness using Photovoice and content analysis. Issue 5 (25th May 2021) - McKinsey, Eva; Pruitt, Anna S.; Austin, Tien
Abstract: In this multipart study, participants in a Housing First program on the Island of O'ahu conducted a Photovoice project involving participatory analysis to investigate the recovery process from homelessness several years after being housed. University researchers then conducted a secondary analysis of the Photovoice study content to expand on findings and examine the unique contributions of the different methods. Findings suggest that individuals who have experienced homelessness will likely need continued support, particularly social support and opportunities for community engagement, well after initial housing. Findings also suggests that a combination of iterative analytic methods that remain participatory may be most useful for examining lived experiences of individuals recovering from homelessness. The study represents a participatory investigation of recovery from homelessness, as well as a rigorous inquiry into the research methods best suited to investigate this lived experience.